Pengembangan Sistem Pencarian Rekan Kerja dalam Praktik Kerja Lapangan dan Kompetisi di Lingkungan Universitas Brawijaya - Joel Johanes Cirio; Denny Sagita Rusdianto; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In the process of student learning at Brawijaya University, every student who is required to undergo one of the courses, namely Field Work Practices (PKL), in some faculties is given the name of the Real Work Lecture (KKN). The purpose in undergoing PKL is to combine hard skills and soft skills obtained during college. This PKL or KKN can also be completed through an achievement track, which is obtained by winning a competition that is suitable for the student's field of learning. In undergoing PKL or KKN, students can choose friends to be a group in undergoing PKL or KKN and Contests. This choice of friends causes several problems for some students, such as the difficulty of finding friends if you don't have many friends, the difficulty of finding friends from different faculties, finding experienced friends, and low pool in friends. Based on these problems, this study aims to build a system that can thrive students to find colleagues in the field of PKL or KKN and competitions. The system's built by using a development method called Waterfall. In the requirements engineering process, there are 52 functional requirements and 1 non-functional requirement. In the design and implementation process, it's being built on the Android operating system using the Kotlin programming language. Laravel framework framework used in building services on this system. In the tests that have been run, all functions are made to run properly with validation testing that gets a valid value of 100% and for compatibility testing, the system that has been created can be run in the Android operating system versions 5.0 to 10.0.